Views of Turkish healthcare professionals and their hesitations about the COVID-19 vaccine - Kükrer, Sadik; Pepekal Kükrer, Ayfer; Arlıer, Sefa; Genç, Simten (Journal of Surgery and Medicine, 2021)
Background/Aim: Views of health sector workers on the safety and efficacy of a vaccine, which forms the basis of a vaccination program, can affect both the public perception of the vaccine and its implementation in the community. Accordingly, this study aimed to acknowledge potential hesitations of healthcare specialists and their views on the acceptability of a vaccine before initiating a vaccine policy program. Methods: A total of 442 healthcare professionals participated in this study by answering a 24-question survey online from their social media accounts. We analyzed the data and present the descriptive statistics with mean and standard deviation values. We performed t-test analysis and analysis of variance to examine physicians’ attitudes toward vaccines and the coronavirus disease 2019 (COVID-19) infection, based on their demographic, and other characteristics. Tamhane and Sidak paired comparison tests were conducted to determine differences in groups after variance analysis. Results: Of the healthcare professionals, 55.9% agreed that the COVID-19 vaccine would end the pandemic. A total of 72.6% of healthcare workers reported that they were planning to get vaccinated with the free COVID-19 vaccine, which is to be distributed by the Ministry. The biggest drawback of the vaccination was its unknown long-term side effects. We noted a difference in the attitude toward vaccines in those older than 41 years and younger than 30 years of age. We also found a significant and positive relationship between the attitudes of the participants toward the measures taken regarding the COVID-19 infection and their attitudes toward the vaccine. Conclusion: Hesitation about a vaccine during a pandemic is a major obstacle to implementing vaccination campaigns. To continue the benefits of vaccination programs, understanding and addressing these hesitations held by healthcare professionals are crucial to the successful implementation of a vaccination program.